The Development of a Creative Learning Community Model to Enhance Students' Quality of Life Based on the Ethical Economy Principles of Schools in Khon Kaen Province - Namseethan, Somkhuan; Ruangsan, Niraj (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were to: (1) study the current conditions of the creative learning community, (2) develop a model of the creative learning community, and (3) evaluate the developed model of the creative learning community for enhancing learners’ quality of life based on the principles of the moral economy in schools in Khon Kaen Province. The research was conducted using the Research and Development (R&D) methodology, consisting of four phases: studying the current situation, developing the model, verifying the appropriateness of the model, and evaluating the effectiveness of the model. The population comprised 3,253 school administrators and teachers in Khon Kaen Province. The sample group consisted of 346 administrators and teachers, selected by simple random sampling. The key informants included 10 administrators and teachers, while the focus group participants consisted of 8 individuals-administrators, teachers, experts, and stakeholders-selected by purposive sampling. The research instruments were a five-point Likert scale questionnaire (reliability = .95), a model validation checklist with a user manual, and a five-point Likert scale model evaluation form (reliability = .90). The data were analyzed using descriptive statistics (frequency, percentage, mean, and standard deviation) and Exploratory Factor Analysis (EFA). The adequacy of sampling and construct validity were verified using the Kaiser-Meyer-Olkin (KMO) measure and Bartlett’s Test of Sphericity. The research findings revealed that: 1. The creative learning community for enhancing learners’ quality of life based on the moral economy consisted of 69 indicators categorized into eight components: (1) shared leadership, (2) participation, (3) collaborative learning, (4) shared vision, (5) benevolent community, (6) community management structure, (7) monitoring and evaluation, and (8) administrative outcomes. 2. The developed model consisted of these eight components, and its appropriateness, as evaluated by experts, was rated at a high level. 3. The overall evaluation results indicated that the model was rated at a high level across all aspects, arranged in descending order of mean scores as follows: usefulness, appropriateness, accuracy, and feasibility. The findings suggest that the developed creative learning community model can be effectively applied to promote learning management and enhance learners’ quality of life in accordance with the moral economy principles.